2017
DOI: 10.1021/acs.nanolett.7b00561
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Two-Dimensional Homologous Faults and Oxygen Electrocatalytic Activities in a Perovskite Nickelate

Abstract: Atomic-scale direct probing of active sites and subsequent elucidation of the structure-activity relationship are important issues involving oxide-based electrocatalysts to achieve better electrochemical conversion efficiency. By generating Ruddlesden-Popper (RP) two-dimensional homologous faults via simple control of the cation nonstoichiometry in LaNiO thin films, we demonstrate that strong tetragonal distortion of [NiO] octahedra is induced by more than 20% elongation of Ni-O bonds in the faults. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 47 publications
(55 reference statements)
0
69
0
Order By: Relevance
“…ε xx is virtually zero across the 5-nm NNO film, showing a good in-plane lattice match between film and substrate, in agreement with the X-ray diffraction data. A thicker NNO film on LAO substrate also shows ε xx = 0 across most of the film, but it starts showing small regions with Ruddlesden-Popper (RP) faults, often reported in nickelates 52 , as seen in Fig. 4c, d.…”
Section: Resultsmentioning
confidence: 77%
“…ε xx is virtually zero across the 5-nm NNO film, showing a good in-plane lattice match between film and substrate, in agreement with the X-ray diffraction data. A thicker NNO film on LAO substrate also shows ε xx = 0 across most of the film, but it starts showing small regions with Ruddlesden-Popper (RP) faults, often reported in nickelates 52 , as seen in Fig. 4c, d.…”
Section: Resultsmentioning
confidence: 77%
“…Similarly, Zhang and co‐workers discovered that ultrathin δ‐MnO 2 nanosheet arrays with abundant oxygen vacancies could give rise to half‐metallicity properties and strong H 2 O adsorption, leading them to exhibit superior OER and hydrogen evolution reaction activities in comparison with their counterparts and bulk δ‐MnO 2 . In addition, Chung and co‐workers found that the Ruddlesden–Popper 2D homologous faults can distort or elongate [NiO 6 ] octahedral in LaNiO 3 thin films and make them possess enhanced catalytic performance toward OER . These outstanding works demonstrate that engineering defects is a feasible and enticing avenue for developing advanced OER catalysts to use in water splitting or other technological fields.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, various perovskite ABO 3 materials (e.g., LaNiO 3 , LaCoO 3 , etc.) have been synthesized and tested for OER in the last few years . However, large bulk particles are the typical existence form of perovskite oxides that lack a large portion of active sites on surface.…”
Section: Introductionmentioning
confidence: 99%
“…have been synthesized and tested for OER in the last few years. [14][15][16][17][18] However, large bulk particles are the typical existence form of perovskite oxides that lack a large portion of active sites on surface. As the electrochemical OER is a featured surface reaction, as a result, the bulk structure with a low specific surface area usually exhibits a low mass activity.…”
Section: Introductionmentioning
confidence: 99%